VD_FINDINFO Jug / 2018 / 138 vom 18. Oktober 2017 - VD Tribunal cantonal (2017)
MEURTRE, TENTATIVEDROIT PÉNAL, DOL ÉVENTUEL, FIXATION DE LA PEINE | 139 CP, 144 al. 1 CP, 22 ad 111 CP, 19a ch. 1 LStup, 115 al. 1 let. b LEtr